Evaluation of TaMFT-3A and TaMKK3-4A alleles on wheat pre-harvest sprouting - Zhang, Bo-Wen; Yang, Bai-Song; Wan, Xiao-Neng; Ma, Xin; Lyu, Kai-Di; Wang, Han; Yang, Shu-Ying; Zhang, Hui-Hui; Hao, Shu-Nv; Ma, Jian; Sun, Guo-Zhong (Frontiers in Plant Science, 2025)
Pre‐harvest sprouting (PHS) is a significant challenge affecting global production of wheat (Triticum aestivum L.). Resistance to PHS is governed by both genetic and environmental factors, making reliable molecular markers essential for enhancing PHS resistance through molecular marker‐assisted selection (MAS). Genes TaMFT-3A and TaMKK3-4A have been cloned in wheat and are known to regulate PHS resistance in white-grained varieties. In this study, we assessed the allelic variations in these genes and their combined effects on PHS resistance using two recombinant inbred line (RIL) populations, Wanxianbaimaizi/Zhongyou 9507 (WZ) and Wanxianbaimaizi/Jing 411 (WJ), under two distinct field environmental conditions. PHS resistance was assessed by measuring seed germination in physiologically mature stage, correlation and ANOVA were used to analyze PHS data. The germination percentage (GP) and germination index (GI) were significantly correlated across both RIL populations. Specific allelic variations at positions -222, +646, and +666 in the TaMFT-3A gene strongly correlated with PHS resistance. The CGA haplotype at these loci was linked to the highest resistance, while the TAA haplotype was associated with the lowest resistance levels. Additionally, haplotype variation at the +660 locus of TaMKK3-4A demonstrated a weak but environmentally modulated correlation with PHS resistance. This study provides a theoretical foundation for utilizing TaMFT-3A and TaMKK3-4A in molecular breeding strategies to enhance wheat resilience to PHS.